2021
DOI: 10.1177/08997640211034580
|View full text |Cite
|
Sign up to set email alerts
|

Informal Volunteering, Inequality, and Illegitimacy

Abstract: This article argues that informal volunteering (the unstructured giving of one’s time to help friends, neighbors, or community) has been ignored or understudied within research and policy. With data frequently showing higher rates of informal volunteering among women, people of color, working-class communities, and other often discriminated against groups and qualitative research demonstrating the value of informal volunteering within poorer communities, such positioning serves to reproduce dominant narratives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…If so, the use of volunteering must be maximised to help reduce health inequalities. It is key to note that those of lower SES are more likely to engage in informal volunteering, which is often overlooked by the volunteering literature (Dean, 2022 ). Thus, it is important that future research further explore the influence of the formality of volunteering on the health benefits, as the current umbrella review found inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…If so, the use of volunteering must be maximised to help reduce health inequalities. It is key to note that those of lower SES are more likely to engage in informal volunteering, which is often overlooked by the volunteering literature (Dean, 2022 ). Thus, it is important that future research further explore the influence of the formality of volunteering on the health benefits, as the current umbrella review found inconsistent results.…”
Section: Discussionmentioning
confidence: 99%
“…From the individual experiences, convergences and divergences have been identified and three superordinate themes emerged from the data: Productivity, Ownership, and Interconnectedness . These themes have been discussed within the context of the data and existing literature, suggesting areas for future research relating not only to demographic characteristics but also to volunteering and unpaid care work, as the relationship between ‘work’ in this context and health and wellbeing appears a complex one, especially considering debates around the politics of care and the political economy of ageing [ 75 , 76 ].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, informal volunteering plays a more significant role in the lives of traditionally disadvantaged and socially discriminated against groups (e.g. people of colour) than those in hegemonic social groups (Dean, 2021 ). Therefore, as an activity that is easier to access without bureaucracy associated or transportation arrangement needed, informal volunteering (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, informal volunteering plays a more significant role in the lives of traditionally disadvantaged and socially discriminated against groups (e.g. people of colour) than those in hegemonic social groups (Dean, 2021).…”
mentioning
confidence: 99%